2019
DOI: 10.1097/qad.0000000000002175
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of resilience resources, antiretroviral therapy initiation, and HIV-1 RNA suppression among people living with HIV in South Africa

Abstract: Objective: Failure to initiate antiretroviral therapy (ART) and achieve virologic suppression are significant barriers to the United Nations 90-90-90 goals. Identifying resilience resources, or modifiable strength-based factors, among people living with HIV is critical for successful HIV treatment and prevention. Design: Prospective cohort study. Methods: From July 2014 to July 2015, 500 adults presenting for voluntary counseling and HIV testing who were diagnosed with HIV and were ART-eligible in South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…As a result, other avenues of mitigating violence against youth, and the poor psychological outcomes stemming from experienced violence, must be explored. Social support, resilience and selfesteem have been found to improve mental health [9,[17][18][19][20][21][22] and HIV care outcomes [23][24][25][26][27]. These domains could serve as potential intervention targets for mitigating the negative psychological effects of violence in YLWH.…”
mentioning
confidence: 99%
“…As a result, other avenues of mitigating violence against youth, and the poor psychological outcomes stemming from experienced violence, must be explored. Social support, resilience and selfesteem have been found to improve mental health [9,[17][18][19][20][21][22] and HIV care outcomes [23][24][25][26][27]. These domains could serve as potential intervention targets for mitigating the negative psychological effects of violence in YLWH.…”
mentioning
confidence: 99%
“…Thirty‐nine studies reported on initiation of ART [2,21,23,28,33,34,37,40‐42,44‐47,49‐54,23,55‐62,64,66,67‐75], with 25 (64%) defining numerators and denominators. Thirty‐two were longitudinal, four of mixed design and three were cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Significant attrition from the care cascade has been documented consistently throughout the region, despite sweeping changes made to increase access to and availability of antiretroviral therapy (ART) [3][4][5][6][7]. A recent prospective cohort study of 500 PWH presenting for testing in Soweto and Gugulethu townships adds to these data, showing that 62% of treatment-eligible PWH initiated ART, but only 25% had evidence of an undetectable HIV-1 plasma RNA (< 50 copies/ml) within 9 months of testing [8,9].…”
Section: Introductionmentioning
confidence: 99%